EVALUATION OF PHYTOCHEMICALS INTERRELATED TO ANTIOXIDANT POTENTIAL OF UNANI PLANTS - MEHAR D. KALIM; D. DUTTA; P. DAS; S. CHATTOPADHYAY (International Journal of Pharma and Bio Sciences, 2015)
Cleome icosandra, Rosa damascena and Cyperus scariosus used extensively in Unani system of medicine to combat various ailments. Extracts of these plants were also noted with antioxidant potential. However, evaluation of bioactive composition of active fractions is essential for its future exploitation as a health-promoting natural product. IC50 values of n-butanol and chloroform fractions derived from crude extracts and scavenging of DPPH, ABTS, •OH, O2•−, ONOO− and •NO, were determined. These active fractions exhibited oxidative DNA damage preventive activity and significant FRAP. No cytotoxicity against U937/PBMC cell lines was noted. Total phenolic and flavonoid content of active fractions was measured. Various phytochemicals viz. quercetin, quercetin-3-o-rutinoside, quercetin-3-o-glucoside, linoleic acid, oleanolic acid, sitosterol, cleomiscosin A and C etc. were identified by ESI-MS analysis of these active fractions and contributing towards the natural antioxidant activity of C. icosandra, R. damascena and C. scariosus, revealed their potential as a functional food.